Processes of Change and Nonsuicidal Self-Injury: A Qualitative Interview Study With Individuals at Various Stages of Change. (June 2019) - Kruzan, Kaylee Payne; Whitlock, Janis
Nonsuicidal self-injury (NSSI) is a pervasive and potentially lethal behavior that affects many youth and adolescents. Effective treatment and prevention efforts are critical but often lack a nuanced understanding of the behavior change process. To address this gap, this research employs a stage of change model to identify and understand the most salient and widespread processes that facilitate NSSI behavior change. Thirty-one semi-structured interviews were conducted with individuals with current or past self-injury. Individuals were recruited to represent all stages of change including those who have not thought about changing behavior to those who have been NSSI-free for years. We employ a directed content analysis to code for dimensions derived from the model and an inductive approach to surface more nuanced change levers. Four organizing dimensions emerged: relational, behavioral, self-knowledge, and barriers . Common change levers of value in clinical practice or in intervention modalities are discussed.